Evaluating the Economic Implications of Local Content in Nigeria’s Sustainable Housing Development Mantra: A Cost-Benefit Approach - K., Agwu; K., Okechukwu; I. G., Ogburie; O. P., Ezirim (International Journal of Real Estate, 2025)
This paper sets out to evaluate the economic implications of local contents in Nigeria’s sustainable housing development mantra using a cost-benefit approach. It notes that there is a big issue of housing affordability in Nigeria due largely to the rising cost of housing construction and the cost of building materials that have remained on the rise. The issue of housing accessibility is also of great concern in Nigeria. It is suggested that over reliance on foreign building materials, manpower, methods and equipment contribute to the high cost of construction in the country. The paper considered the cost effectiveness of incorporating local content in sustainable housing development in Nigeria. It adopts deskwork research approach; relying on secondary data to reach its conclusion. It also explores the cost-benefit approach for adopting local content policies in sustainable housing development, and concludes that the benefits for adopting local content policies in sustainable housing development in Nigeria are many. The costs involved in implementing local content policies are surmountable thereby encouraging the implementation of such a policy in the country. The economic implications for adopting this policy are found to be job creation opportunities, economic diversification, cost saving, increased local investment, reduction in poverty among others. The study recommends a people-minded political leadership for the country; leadership that could be innovative enough to consider the people’s welfare as prime. Such leadership will consider various ways of making life easier and cheaper for the citizenry.
Keywords: Economic Implications; Local Content; Sustainability; Housing Development; Cost-Benefit